THE LONELINESS OF A FEMALE CHARACTER IN RACHAEL LIPPINCOTT ET. AL.’S NOVEL FIVE FEET APART - Della Muftafrisda Arifia; Erika Citra Sari Hartanto (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
This study focuses on the loneliness that is faced by the female main character, Stella Grant, in the Five Feet Apart novel. There are two focuses in analyzing this study, the first is the causes of Stella Grant’s loneliness, and the second is the copes of Stella Grant’s loneliness. To analyze this study, the writer uses loneliness theory by Peplau & Perlman (1979 & 1981). The writer uses a psychoanalysis approach about loneliness theory. The author’s narration and also dialogue in the novel help the writer to know the causes and the copes of the loneliness that Stella Grant faced that is suitable with the theory. The causes of loneliness are physical separation, death, unemployment, and the end of the relationship. The biggest influence that causes Stella to feel lonely is due to physical separation and the death of the closest person. Physical separation makes her feel alone and abandoned. While the death of the closest person makes her lose her direction and lack the spirit of life. The copes of loneliness are adaptation, task choice, and standards for evaluating social relationships, ways of using existing relationships more fully, ways of forming new relationships, and replacement relationships. Meanwhile, the way that gives the big impact for Stella to overcome her loneliness is forming a new relationship and task choice. Forming a new relationship helps Stella to find someone new in her life so it can give a new color to her life. Then, task choice can help her be busier and forget her loneliness.